Penerapan Media Pembelajaran Flash Card Untuk Meningkatkan Perkembangan Bahasa Anak Usia Dini - Mamima Laulet; Melani Nees; Marselmi Neno Uran; Mariam Klomang; Junirna A. Knaufmone; Oreasa Bernadus Tuauni; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
This study aims to determine the effect of flashcard learning media on the language development of early childhood aged 4–6 years at Kasih Karunia Kindergarten. This study uses a quantitative method with a quasi-experimental design. The research subjects consisted of 20 children aged 4–6 years using total sampling technique. Data collection techniques used observation and questionnaires based on early childhood language development indicators in accordance with Permendikbud Number 137 of 2014. Data were analyzed using descriptive analysis and simple linear regression. The results showed that most children were in the high and moderate categories of language development, with the use of flashcards contributing 61.1% to children's language development. These findings indicate that the use of flashcards as a concrete, visual, and attractive learning medium can improve children's ability to understand vocabulary, express opinions, and communicate verbally. Thus, flashcards are proven to be effective in supporting the language development of early childhood and are recommended for creative and continuous use in the learning process.